Tambal redevelopment of Trece Martires Public Market - Roxas, Paul Brian Kyle E. (College of Architecture, University of the Philippines Diliman, 2023)
Public markets have always served as centers for economic exchange, offering the best and freshest products of what each region, city, or town has to offer. Sadly, an increasing number of public markets are falling into despair with poor maintenance, sanitation, and not keeping up with the rapid changes in the urban environment brought by advancements in technology. Local markets not only serve as a center for local trade, but also an avenue for social exchange which caters to users from all walks of life. Trece Martires City, well-known for its proximity to centers for commerce and accessibility to its neighboring communities, faces an unprecedented growth with its local economy. And with its location being in an urban zone for development, the public market in the city seeks the need for rehabilitation to adapt with these changes. Understanding the grounds for improvement and concerns within the structure through on-site observations and interviews with the current stakeholders was used as a guide in the entire design process. The proposed architectural project is reimagined with an emphasis on the proper integration of spaces that would address to the present needs of its users and the improvement of market establishments to strengthen their presence in the local trading scene resulting to the adaptability and survival of public markets with the rapid changes in our present urban landscape.